2009
DOI: 10.1089/jmf.2008.0128
|View full text |Cite
|
Sign up to set email alerts
|

Cassia Cinnamon for the Attenuation of Glucose Intolerance and Insulin Resistance Resulting from Sleep Loss

Abstract: Epidemiological investigations reveal a concomitant increase in sleep loss and metabolic diseases, including type 2 diabetes mellitus, over the past several decades. An increasing body of scientific evidence indicates that acute sleep loss induces insulin resistance and glucose intolerance profiles similar to those of type 2 diabetes mellitus patients. Experimentally, cassia cinnamon (Cinnamomum cassia) supplementation facilitates glucose disposal in healthy humans, which may be achieved by enhancing (1) insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Furthermore, studies using type II diabetic animals reported anti-diabetic effects of cinnamon extract administered at 200 mg/kg for 6 weeks [59]. Multiple human clinical trials have also provided evidence for anti-diabetic effects of cinnamon in patients and healthy subjects [60][66]. Mechanistic studies of several biomarkers suggest that the effect of cinnamon is mediated via regulation of multiple genes involved in insulin sensitive and lipogenesis pathways [67][69].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies using type II diabetic animals reported anti-diabetic effects of cinnamon extract administered at 200 mg/kg for 6 weeks [59]. Multiple human clinical trials have also provided evidence for anti-diabetic effects of cinnamon in patients and healthy subjects [60][66]. Mechanistic studies of several biomarkers suggest that the effect of cinnamon is mediated via regulation of multiple genes involved in insulin sensitive and lipogenesis pathways [67][69].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported that cinnamon and its extracts possess the capacity to enhance insulin sensitivity and insulin secretion. 186 Administration of C. cassia and zeylanicum extracts was found to increase plasma insulin in rats. 187 Polyphenols from cinnamon restored pancreatic weight and alleviated mesenteric white fat accumulation related to improved insulin sensitivity in high fat/high fructose (HF/HF)fed rats.…”
Section: Enhancement Of Insulin Sensitivity and Insulin Secretionmentioning
confidence: 99%
“…Most of the studies in humans involving the effects of spices on obesity and diabetes have tested cinnamon (40, 47, 61, 73, 88, 99, 154, 158, 173, 174, 216). All these studies suggested that cinnamon modulated the levels of various biomarkers linked with insulin resistance and obesity favorably.…”
Section: Human Studiesmentioning
confidence: 99%